Praktik Toleransi Antar Umat Beragama Perspektif Pendidikan Islam pada Masyarakat Mahakarya Kampung I dan II, Kecamatan Luhak Nan Duo - Sri Rahayu; Ahmad Kosasih (ISLAMIKA, 2022)
This study aims to find out how the practice of tolerance, the contribution of Islamic education and the obstacles faced in the life of tolerance between religious communities in Mahakarya Kampung I and II, Luhak Nan Duo District, West Pasaman Regency. This study uses a qualitative method with the type of research that is phenomenology. Data collection techniques used are observation, interviews and documentation. The results of this study indicate that the practice of tolerance is running well and in accordance with the boundaries, namely in the field of muamalah. The contribution of Islamic education in maintaining tolerance is by instilling an attitude of respect, acceptance, and acknowledgment that there is religious diversity in Mahakarya Kampung I and II through formal Islamic education in the school environment, non-formal Islamic education in the community such as MDA and informal education, namely education from family. The obstacles faced in tolerance in the Masterpieces of Kampung I and II are not too obvious, because the tolerance in the village is so good that it was named the Village of Awareness of Harmony in 2021.